A theoretical framework proposal for analysis of experience in immersive journalism - dos Anjos Fonseca, Adalton (2020)
This article aims to propose a theoretical framework for the analysis of experience in immersive journalism. It starts with the discussion about the relationship between immersion and journalism and the concepts of experience and immersive journalism. The methodology consists of a combination of bibliographic research and product analysis. The theoretical framework proposal is based on four levels: epistemic, strategic, stylistic and aesthetic - that unfold in theoretical and technical aspects. Among the conclusions, these levels show an interrelationship of experiences of agents who share their emotions, repertoires, worldviews and experiences.